2010
DOI: 10.1103/physrevb.81.195201
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear pressure dependence of the direct band gap in adamantine ordered-vacancy compounds

Abstract: A strong nonlinear pressure dependence of the optical absorption edge has been measured in defect chalcopyrites CdGa 2 Se 4 and HgGa 2 Se 4 . The behavior is due to the nonlinear pressure dependence of the direct band-gap energy in these compounds as confirmed by ab initio calculations. Our calculations for CdGa 2 Se 4 , HgGa 2 Se 4 and monoclinic ␤-Ga 2 Se 3 provide evidence that the nonlinear pressure dependence of the direct band-gap energy is a general feature of adamantine ordered-vacancy compounds irresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 21 publications
5
53
0
Order By: Relevance
“…11). In our previous work, 16 we suggested that the strong nonlinear pressure dependence of the direct bandgap is a general feature common to all OVCs due to a conduction band anticrossing at the C point of the Brillouin zone caused by two facts: (i) the presence of ordered vacancies in adamantine OVCs and (ii) the doubling of the unit cell along the c axis with respect to the zinc blende structure.…”
Section: First Upstrokementioning
confidence: 99%
See 4 more Smart Citations
“…11). In our previous work, 16 we suggested that the strong nonlinear pressure dependence of the direct bandgap is a general feature common to all OVCs due to a conduction band anticrossing at the C point of the Brillouin zone caused by two facts: (i) the presence of ordered vacancies in adamantine OVCs and (ii) the doubling of the unit cell along the c axis with respect to the zinc blende structure.…”
Section: First Upstrokementioning
confidence: 99%
“…It can be observed that the edge shifts to higher energies below 8 GPa, and it shifts to lower energies from 8 GPa till 16 GPa. In our previous work, 16 we explained that the optical absorption edge of DCCdGa 2 Se 4 and DC-HgGa 2 Se 4 was of direct character and that the direct bandgap shows a strong non-linear pressure dependence at low pressures. Figure 11 shows the pressure dependence of the experimentally estimated direct bandgap energy (circles) in DC-CdGa 2 Se 4 , as obtained by extrapolating the linear fit of the high-energy part of the (ah ) 2 versus h plot to zero absorption.…”
Section: First Upstrokementioning
confidence: 99%
See 3 more Smart Citations